Validitas Lembar Kerja Peserta Didik Biologi Terhadap Keterampilan Berpikir Kritis Jenjang SMP - Mili Yana; Muhammad Zaini; Dharmono Dharmono (Universitas Sebelas Maret, 2021)
This development research aims to evaluate the validity of Biology worksheets on thinking Critical for Class VIII Junior High School Students. LKPD biology is the result of the development of the concepts of systems in the human body, namely 1) the movement system, 2) the digestive system, and 3) the circulatory system. Research development using the Tessmer Model. The research is focused on the first micro cycle, which is about validity. The research was carried out for six months (July-December 2021) at Hasbunallah Middle School, Tabalong Regency. The research subjects to carry out content validity were three lecturers of the ULM science teacher master's degree. Aspects that are validated are the appropriateness of content, language, presentation and graphics. The data obtained from the research instrument in the form of a validity assessment sheet. Data analysis was done descriptively. The results showed that the validity based on the results of the expert team's validation had an average score of 75.00% with a fairly valid category, which could be used with slight revisions. LKPD can already be used in biology learning at school after revision, and is eligible to continue on individual tests.